Field verification of thermal energy meters through ultrasonic clamp-on master meters. (February 2020) - Ficco, G.; Frattolillo, A.; Malengo, A.; Puglisi, G.; Saba, F.; Zuena, F.
Highlights: In service verification of thermal energy meters is mandatory in several EU countries. Strict error and uncertainty limits are required for thermal energy meters verification. Results of experimental campaigns in laboratory and in-field are presented. The uncertainty budget of ultrasonic clamp-on flow meters is presented. Although promising, the ultrasonic clamp-on technique presents metrological criticalities. Abstract: The measurement of heat consumption in buildings through thermal energy meters presents numerous metrological issues due, for example, to the installation and operational conditions (e.g. presence of plant constraints, low flow rates, low temperature differences between flow and return) leading often to unacceptable measurement errors and uncertainties. Therefore, in several EU countries, to guarantee consumer protection it is mandatory to carry out periodic inspection both in the laboratory and in the field to assess their accuracy, while in service. In this work, the authors present the results of experimental campaigns aimed at analysing the key metrological concerns for clamp-on master meters during in-field verification of thermal energy meters. The results showed that particular care should be paid to the meter configuration and installation of the transducer and that legal metrology statutes in terms of permissible error and uncertainty for fielded meters are often very difficult to comply with.